2018
DOI: 10.1038/gim.2018.33
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic expansion illuminates multilocus pathogenic variation

Abstract: PurposeMultilocus variation-pathogenic variants in two or more disease genes-can potentially explain the underlying genetic basis for apparent phenotypic expansion in cases for which the observed clinical features extend beyond those reported in association with a "known" disease gene.MethodsAnalyses focused on 106 patients, 19 for whom apparent phenotypic expansion was previously attributed to variation at known disease genes. We performed a retrospective computational reanalysis of whole-exome sequencing dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
136
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 120 publications
(141 citation statements)
references
References 37 publications
4
136
1
Order By: Relevance
“…Other variants of interest that were found during the course of ES or GS are listed in Table S2, with the most notable among these being: (a) a RAC1 de novo variant, c.116A>G p.(Asn39Ser) in Individual 3, with in silico modeling, mouse fibroblasts spreading assays, and in vivo overexpression assays in zebrafish having demonstrated that this variant functions as a dominant‐negative allele, resulting in microcephaly, reduced neuronal proliferation, and cerebellar abnormalities in vivo (Reijnders et al, ); (b) a HNRNPU de novo c.837_839delAGA variant in Individual 11, leading to deletion of glutamic acid at position 279, with LOF mutations associated with ID (Bramswig et al, ; Hamdan et al, ; Leduc et al, ; Yates et al, ); and (c) a genetically confirmed diagnosis of mucopolysaccharidosis type IIIA—Sanfilippo syndrome due to compound heterozygous mutations in SGSH in Individual 14‐1. It is well known that multiple molecular diagnoses can be found during the course of ES or GS, and it is likely that the clinical presentation is a blended phenotype in any given individual (Karaca et al, ; Posey et al, ). To be conservative in our assignment of “pathogenicity” using the ACMG/AMP framework (Richards et al, ), we have included for these cases the criterion of “BP5‐Variant found in a case with an alternate molecular basis for disease” in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other variants of interest that were found during the course of ES or GS are listed in Table S2, with the most notable among these being: (a) a RAC1 de novo variant, c.116A>G p.(Asn39Ser) in Individual 3, with in silico modeling, mouse fibroblasts spreading assays, and in vivo overexpression assays in zebrafish having demonstrated that this variant functions as a dominant‐negative allele, resulting in microcephaly, reduced neuronal proliferation, and cerebellar abnormalities in vivo (Reijnders et al, ); (b) a HNRNPU de novo c.837_839delAGA variant in Individual 11, leading to deletion of glutamic acid at position 279, with LOF mutations associated with ID (Bramswig et al, ; Hamdan et al, ; Leduc et al, ; Yates et al, ); and (c) a genetically confirmed diagnosis of mucopolysaccharidosis type IIIA—Sanfilippo syndrome due to compound heterozygous mutations in SGSH in Individual 14‐1. It is well known that multiple molecular diagnoses can be found during the course of ES or GS, and it is likely that the clinical presentation is a blended phenotype in any given individual (Karaca et al, ; Posey et al, ). To be conservative in our assignment of “pathogenicity” using the ACMG/AMP framework (Richards et al, ), we have included for these cases the criterion of “BP5‐Variant found in a case with an alternate molecular basis for disease” in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Other variants of interest that were found during the course of ES or GS are listed in Table S2, with the most notable among these being: (a) a heterozygous mutations in SGSH in Individual 14-1. It is well known that multiple molecular diagnoses can be found during the course of ES or GS, and it is likely that the clinical presentation is a blended phenotype in any given individual (Karaca et al, 2018;Posey et al, 2017). To be conservative in our assignment of "pathogenicity"…”
Section: Taf1 Variantsmentioning
confidence: 99%
“…Bioinformatic analyses (SIFT, PolyPhen2, MutationTaster, CADD, and PhyloP) were used to predict the potential deleterious or pathogenic effect of variants on protein function and also evolutionary conservation. In four subjects (Family 1 individuals II‐1 and II‐2, Family 5 individual II‐1, and Family 6 individual II‐1), absence of heterozygosity (AOH) was determined based on the calculated B‐allele frequency from exome data using an in‐house developed bioinformatic tool, BafCalculator (https://github.com/BCM-Lupskilab/BafCalculator), as previously described 26 . An arbitrary cutoff point or value of 0.5 Mb was used in calculating the size of the AOH, and unphased data or ROH block around the variant as well as the total genomic AOH/ROH.…”
Section: Methodsmentioning
confidence: 99%
“…Exome sequencing (ES) was performed on two affected siblings (BH9685‐1 and BH9685‐4) of Turkish descent who were born to consanguineous parents in Family 1 using our standard sequencing and variant prioritization workflow that has been previously described, including BafCalculator for determination of absence of heterozygosity (AOH), potentially reflecting identity‐by‐descent (IBD), from exome variant data . The proband in Family 2 had commercial panel testing from Invitae (San Francisco, California), the Early Infantile Epileptic Encephalopathy Panel (gene content enumerated alphabetically in Table S1), which includes CACNA2D2 .…”
Section: Methodsmentioning
confidence: 99%
“…(B) Absence of heterozygosity (AOH) plots for Family 1 show that the CACNA2D2 variant lies in a region of AOH in chromosome 3 that is represented by the gray shaded area for both affected siblings (BH9685‐1 and BH9685‐4). AOH regions are calculated using B‐allele frequency data from exome data . (C) T2‐weighted brain MRI images for affected siblings BH9685‐1 and BH9685‐4 show cerebellar atrophy.…”
Section: Methodsmentioning
confidence: 99%